Shoya Ishida’s Altruistic Acts in the Movie “Koe no Katachi” as Education Values - Dimas Rohmat Budiman; Nur Hidayat; Siti Musarokah (Lingua Franca, 2023)
This research aims to discover the altruistic actions performed by Shoya Ishida in the film Koe no Katachi. This study also aims to determine whether altruistic actions can explain educational values. This research is qualitative. The research data is from Shoya Ishida's altruistic actions in the film Koe no Katachi. Data collection techniques using documentation. At the same time, data analysis is done by collecting, reducing, presenting, and drawing conclusions. The study's results stated that Shoya Ishida had carried out altruistic actions that impacted the growth of his friends. This altruistic action can be used as an example of a simple action that can change the lives of others, especially the educational process. The research results also show how important it is to listen and be heard, have empathy, and act to help others and yourself by truly taking action to spread and pursue knowledge so that others can share the same understanding and the same vision to improve humanity as a whole and support each other for the greater good.